2017
DOI: 10.4172/2472-1921.100062
|View full text |Cite
|
Sign up to set email alerts
|

Nitrates, Nitrites and Nitrosamines from Processed Meat Intake and ColorectalCancer Risk

Abstract: The International Agency for Research on Cancer reported that eating processed meat can increase a person's risk for colorectal cancer and classified processed meat as carcinogenic to humans. Nitrate and nitrite are used as additives to improve food quality and protect against microbial contamination and are sources of N-nitroso compounds (NOCs) which are known carcinogens. This review outlines the association between processed meat intake and colorectal cancer risk and discusses the use of nitrates and nitrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 25 publications
0
46
0
1
Order By: Relevance
“…The (probably) carcinogenic property of processed and red meat could be ascribed to the toxicants that arise during the production process (Bouvard et al, 2015;Johnson, 2017) as well as the presence of rich saturated fatty acids (Wolk, 2017) within these products. Polycyclic aromatic hydrocarbons (PAHs) (Ledesma, Rendueles, & Díaz, 2016;Nisha, Kumar, Arivudainambi, Umer, & Khan, 2015), N-nitrosamines (Cantwell & Elliott, 2017;Herrmann, Duedahl-Olesen, & Granby, 2015), and heterocyclic aromatic amines (HAAs) (ur Rahman, Sahar, Khan, & Nadeem, 2014;Raza, Shabbir, Khan, Suleria, & Sultan, 2015) are well-known mutagenic agents that are typical process-induced toxicants in meat products. It has also been well confirmed that those with diets high in saturated fatty acids have a higher risk for chronic diseases due to an increased presence of low-density lipoproteins in the body (Ruiz-Núñez et al, 2014;Siri-Tarino, Sun, Hu, & Krauss, 2010).…”
Section: The Health Concerns Of Traditional Meat Consumptionmentioning
confidence: 99%
“…The (probably) carcinogenic property of processed and red meat could be ascribed to the toxicants that arise during the production process (Bouvard et al, 2015;Johnson, 2017) as well as the presence of rich saturated fatty acids (Wolk, 2017) within these products. Polycyclic aromatic hydrocarbons (PAHs) (Ledesma, Rendueles, & Díaz, 2016;Nisha, Kumar, Arivudainambi, Umer, & Khan, 2015), N-nitrosamines (Cantwell & Elliott, 2017;Herrmann, Duedahl-Olesen, & Granby, 2015), and heterocyclic aromatic amines (HAAs) (ur Rahman, Sahar, Khan, & Nadeem, 2014;Raza, Shabbir, Khan, Suleria, & Sultan, 2015) are well-known mutagenic agents that are typical process-induced toxicants in meat products. It has also been well confirmed that those with diets high in saturated fatty acids have a higher risk for chronic diseases due to an increased presence of low-density lipoproteins in the body (Ruiz-Núñez et al, 2014;Siri-Tarino, Sun, Hu, & Krauss, 2010).…”
Section: The Health Concerns Of Traditional Meat Consumptionmentioning
confidence: 99%
“…While further research must be done, studies have suggested that nitrates and nitrites, common chemical preservatives added to meat, may be the culprit. In the body these preservatives can lead to the formation of N-nitroso-compounds (NOCs), which suggests a possible association between NOCs and a higher incidence of gastrointestinal cancer, specifically rectal cancer [13].…”
Section: Ecosystem and Cancermentioning
confidence: 99%
“…This is due to curing using nitrite which can be a pre-cancerous carcinogenic effect because it will react with amines or amides amine from animal protein components to form nitrosamine compounds [5]. Nitrosamine is one of the compounds cause of cancer [6]. Therefore the addition of natural dyes such as red fermented rice is safer and has a more antioxidant and stable red color.…”
Section: Introductionmentioning
confidence: 99%